Perancangan Sistem Customer Relationship Management Berbasis Web - Ardiansyah, Ardiansyah; Askar, Askar; Mashud, Mashud; Awaliah, Neneng (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The development of information technology today is much faster than in previous years, making business people required to follow developments by implementing technology and communication intensively in various sectors. Customer Relationship Management (CRM) is one important aspect in building good relationships between companies and customers.The aims of the study were to design and implement a web-based CRM system that suits the needs of this company, a company that is engaged in the production and sales of furniture. The data was obtained through (1) field research, (2) library research, and (3) The method used in the research is the waterfall system development method by using PHP and MySQL programming languages The results of the study indicate that this system has an average presentation value of 84.07%, indicating that the system is very feasible to implement. This system is able to increase interaction and communication with customers, which in turn significantly increases customer satisfaction and improves the quality of service overall. Thus, this system can be the right solution for this company in overcoming the challenges in the increasingly competitive business era and achieving competitive advantage in the furniture industry.